637 Immune-related adverse events (irAEs) may indicate a favorable prognosis in metastatic renal cell carcinoma (mRCC) patients treated with immune checkpoint inhibitors (ICI). (10th December 2020) - Martini, Dylan; Evans, Sean; Goyal, Subir; Liu, Yuan; Anders Olsen, T; Magod, Benjamin; Brown, Jacqueline; Yantorni, Lauren; Russler, Greta; Caulfield, Sarah; Goldman, Jamie; Nazha, Bassel; et al.
Abstract : Background: Immune checkpoint inhibitors (ICI) have become an increasingly utilized treatment in metastatic renal cell carcinoma (mRCC). Although they have a favorable toxicity profile, immune-related adverse events (irAEs) can have a significant impact on patients' quality of life. It is not well understood whether irAEs are associated with improved clinical outcomes. We investigated the relationship between irAEs and clinical outcomes in mRCC patients treated with ICI. Methods: We performed a retrospective study of 200 patients with mRCC who received ICI at Winship Cancer Institute of Emory University from 2015–2020. Clinical outcomes were measured by overall survival (OS), progression-free survival (PFS), and clinical benefit (CB). OS and PFS were calculated from ICI-initiation to date of death and radiographic or clinical progression, respectively. CB was defined as a best radiographic response of complete response (CR), partial response (PR), or stable disease (SD) for >6 months per response evaluation criteria in solid tumors (RECIST) version 1.1. Toxicity data was collected from clinic notes and laboratory values. The association with OS and PFS was modeled by Cox proportional hazards model. Kaplan-Meier curves were created for survival estimates. Results: Most patients were males (71%), and 78% had clear-cell RCC (ccRCC). Most patients (58%) received anti-PD-1 monotherapy. The majority were international mRCC database consortium (IMDC) intermediate (57%) or poor-risk (26%). Anti-PD-1 monotherapy was the most common (58%) treatment regimen and most patients received ICI as first (38%) or second-line (42%) treatment. One-third of patients (33%) experienced an irAE, with the most common being endocrine (13%), gastrointestinal (11%), and dermatologic (10%). Patients who experienced irAEs had significantly longer OS (HR: 0.52, 95% CI: 0.32–0.87, p=0.013), higher chance of CB (OR: 2.10, 95% CI: 1.11–4.00, p=0.023) and showed a trend towards longer PFS (HR: 0.71, 95% CI: 0.49–1.02, p=0.065) in MVA (table 1 ). Patients who had thyroid irAEs had significantly longer OS, PFS, and higher chance of CB in MVA (table 1 ). The objective response rate was higher for patients who experienced irAEs (34% vs. 18%). Patients who experienced irAEs had significantly longer median OS (44.5 vs. 18.2 months, p=0.005) and PFS (7.5 vs 3.6 months, p=0.0028) compared to patients who did not (figure 1 ). Conclusions: We showed that mRCC patients who experienced irAEs, particularly thyroid irAEs, had improved clinical outcomes. This suggests that irAEs may be prognostic of favorable outcomes in mRCC patients treated with ICI. Larger, prospective studies are needed to validate these findings. Acknowledgements: Research reported in this publication was supported in part by the Breen Foundation and the Biostatistics Shared Resource of Winship Cancer Institute of Emory University and NIH/NCI under award number P30CA138292. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health. Trial Registration: Not applicable Ethics Approval: This retrospective study was approved by the Emory University Institutional Review Board. Consent: Not applicable References: Not applicable